Debonding and Clean-Up in Orthodontics: Evaluation of Different Techniques and Micro-Morphological Aspects of the Enamel Surface - Maurizio D'Amario; Sara Bernardi; Daniele Di Lauro; Giuseppe Marzo; Guido Macchiarelli; Mario Capogreco (MDPI AG, 2020)
There is currently no consensus on the best way to remove adhesive remnants from teeth following debonding. The main objective of this study is to evaluate and compare the effectiveness of four adhesive resin removal (clean-up) techniques, performed with or without the use of an operative microscope. Forty human teeth were duplicated using an epoxy resin for impregnation. Brackets were bonded to teeth and debonded from teeth. Then, the samples were randomly divided into two equal groups-the naked eye group and the magnification group-and further subdivided into four equal subgroups, in order to compare the different techniques used for the clean-up. Each subgroup was formed of five natural teeth with the respective pre- and post-bonding replicas. Macro- and micro-analysis by means of a stereomicroscope and scanning electron microscopy evaluated, qualitatively and quantitatively, the adhesive remnant index and the damage index of the enamel. Overall, the magnification improved the removal of resins compared to the naked eye (p < 0.001), and the use of magnification constantly reduced resin residual and surface damage. Enamel damage and adhesive residual from the clean-up procedures represent an ascertained risk in orthodontics. The use of a magnification system improves the quality of debonding and clean-up techniques in a significant way.